Baram Line or West Baram Line? A Discussion with Late Prof. H.D. Tjia on Its Nomenclature in Jong et al. (2016) - Franz L. Kessler; John Jong (Ikatan Ahli Geologi Indonesia, 2016)
This note summarises the unedited correspondence and discussion we had with late Prof. H.D. Tjia on the above topic, starting with an initial email received by the corresponding author of the article “Structural Development, Deposition Model and Petroleum System of Paleogene Carbonate of the Engkabang-Karap Anticline, Onshore Sarawak” by Jong et al. (2016) published in Berita Sedimentologi, Vol. 34, p. 5-25.